Positive electrode active material, method for preparing same, and positive electrode for lithium secondary battery comprising same, and lithium secondary battery

By using lithium transition metal oxides with manganese content exceeding cobalt content in the positive electrode active material of lithium secondary batteries, and introducing concentration gradients and specific crystal structures into the material, the cost and thermal stability problems caused by high cobalt content are solved, and efficient lithium ion migration and excellent output characteristics are achieved.

CN119786593APending Publication Date: 2025-04-08LG CHEM LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510116402.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-05-11
Filing Date
2019-05-10
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Due to the high cobalt content of the existing lithium secondary batteries, the positive electrode active materials have increased costs and poor thermal stability, and the discharge capacity and output characteristics are reduced when the cobalt content is reduced.

Method used

When the content of manganese exceeds the content of cobalt, at least one element of nickel, cobalt and manganese has a concentration gradient from the center of the particle to the surface, and on the surface of the positive electrode active material, the ratio between the c-axis direction and the growth direction of the particle is 85° to 95° is more than 60%.

Benefits of technology

Even when the cobalt content is reduced, excellent output characteristics and structural stability can be maintained, the manufacturing cost of the battery can be reduced, and the mobility of lithium ions can be improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786593A_ABST
    Figure CN119786593A_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material, a method for preparing the same, and a positive electrode for a lithium secondary battery and a lithium secondary battery comprising the same. The positive electrode active material includes a lithium transition metal oxide in which a content of cobalt is less than a content of manganese, and nickel included in the positive electrode active material has a concentration gradient that gradually decreases from a center of a particle of the positive electrode active material to a surface of the particle, wherein the molar ratio of cobalt: manganese in the lithium transition metal oxide is in the range of 1: 1.8 to 1: 3 or less, the positive electrode active material is in the form of secondary particles formed by aggregation of primary particles, and wherein at least 8 points on the surface of the positive electrode active material, the positive electrode active material is formed from cobalt and manganese. The ratio at which the angle between the c-axis direction measured by TEM analysis and the growth direction of the particles at the measurement point satisfies 85 DEG to 95 DEG is 60% or more. The positive electrode active material of the present invention has excellent output characteristics while having a relatively small cobalt content.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention patent application is a divisional application based on the Chinese invention patent application with application date of May 10, 2019, application number 201980027475.0, and invention name “Positive electrode active material for lithium secondary battery, preparation method thereof, positive electrode for lithium secondary battery and lithium secondary battery containing the positive electrode active material”.

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims the benefit of Korean Patent Application No. 2018-0054292 filed on May 11, 2018, in the Korean Intellectual Property Office, the disclosure of which is incorporated herein in its entirety by reference. Technical Field

[0004] The present invention relates to a positive electrode active material for a lithium secondary battery, a method for preparing the positive electrode active material, and a positive electrode for a lithium secondary battery and a lithium secondary battery comprising the positive electrode active material. Background Art

[0005] As technology develops and demand for mobile devices increases, demand for secondary batteries as energy sources has increased significantly. Among these secondary batteries, lithium secondary batteries with high energy density, long cycle life, and low self-discharge rate have been commercialized and widely used.

[0006] Lithium transition metal composite oxides have been mainly used as positive electrode active materials for lithium secondary batteries, and among these oxides, lithium cobalt oxide (LiCoO2) having high operating voltage and excellent capacity characteristics has been mainly used. However, because lithium cobalt oxide has poor thermal properties due to an unstable crystal structure caused by delithiation and is expensive, there are limitations in using a large amount of lithium cobalt oxide as a power source for medium and large devices such as electric vehicles.

[0007] Recently, various lithium transition metal oxides such as LiNiO2, LiMnO2, LiMn2O4, and LiFePO4 have been developed as materials that replace lithium cobalt oxide and are used in medium-sized and large-sized devices such as electric vehicles. However, the disadvantage of LiNiO2 is that it is difficult to synthesize by a simple solid phase reaction, and its thermal stability and cycle characteristics are inferior to those of LiCoO2. In addition, the limitations of LiMnO2 and LiMn2O4 are that they have lower capacity and poorer high temperature characteristics than LiCoO2. In particular, for LiMn2O4, some LiMn2O4 has been commercialized as a low-cost product, but due to the Mn 3+Poor life characteristics are caused by structural distortion (Jahn-Teller distortion). Currently, a great deal of research has been conducted on the application of LiFePO4 to hybrid electric vehicles (HEVs), but it may be difficult to apply it to other fields due to low ionic conductivity.

[0008] For this reason, a material that has recently received much attention as a cathode active material to replace lithium cobalt oxide is lithium nickel cobalt manganese oxide [Li(Ni o Co p Mn q )O2, where o, p, and q are each independently the atomic fraction of the oxide constituent elements, where 0 < o ≤ 1, 0 < p ≤ 1, 0 < q ≤ 1 and o + p + q = 1].

[0009] Recently, with the increasing interest in electric vehicles, the rising price of cobalt raw materials has become an important issue. It is expected that the price of cobalt raw materials will continue to increase, and therefore, it is necessary to develop a cathode active material with a reduced cobalt content.

[0010] However, the limitation of lithium nickel cobalt manganese oxide is that when the nickel content is the same, the discharge capacity and output characteristics decrease as the cobalt content decreases. Therefore, it is necessary to develop a cathode material that has a small decrease in capacity while maintaining typical output characteristics and has a reduced cobalt content. Summary of the Invention

[0011] Technical Problem

[0012] One aspect of the present invention provides a cathode active material that has excellent output characteristics while having a relatively small cobalt content.

[0013] Another aspect of the present invention provides a cobalt-reduced cathode active material that has excellent structural stability and improved lithium mobility.

[0014] Another aspect of the present invention provides a method for preparing the cathode active material.

[0015] Another aspect of the present invention provides a cathode for a lithium secondary battery, the cathode comprising the cathode active material.

[0016] Another aspect of the present invention provides a lithium secondary battery that comprises the cathode for a lithium secondary battery.

[0017] Technical Solution

[0018] According to one aspect of the present invention, there is provided a positive electrode active material comprising a lithium transition metal oxide having an average composition represented by Formula 1, wherein the content of cobalt in the lithium transition metal oxide is less than the content of manganese, wherein at least one of nickel, cobalt, and manganese in the lithium transition metal oxide has a concentration gradient that gradually changes from the center to the surface of the particle, the positive electrode active material is in the form of secondary particles formed by aggregation of primary particles, and wherein at at least 8 points on the surface of the positive electrode active material, the ratio of the angle between the c-axis direction measured by TEM analysis and the growth direction of the particle at the measurement point that satisfies 85° to 95° is 60% or more:

[0019] [Formula 1]

[0020] Li 1+a Ni x Co y Mn z M 1 w O2

[0021] In Formula 1, 0 ≤ a ≤ 0.3, 0.65 ≤ x < 1, 0 < y ≤ 0.35, 0 < z ≤ 0.35, 0 ≤ w ≤ 0.02 and y < z, and M 1 comprises at least one selected from the following: aluminum (Al), zirconium (Zr), magnesium (Mg), zinc (Zn), yttrium (Y), iron (Fe), and titanium (Ti).

[0022] According to another aspect of the present invention, there is provided a method for preparing a positive electrode active material, the method comprising the steps of: preparing a first transition metal-containing solution and a second transition metal-containing solution, the first transition metal-containing solution containing a nickel raw material, the second transition metal-containing solution having a transition metal concentration different from that of the first transition metal-containing solution and containing a nickel raw material, a cobalt raw material, and a manganese raw material; preparing a positive electrode active material precursor by mixing the first transition metal-containing solution and the second transition metal-containing solution while gradually changing the mixing ratio of the first transition metal-containing solution and the second transition metal-containing solution; and mixing the positive electrode active material precursor with a lithium-containing raw material and sintering the mixture to synthesize the positive electrode active material, wherein the step of preparing the positive electrode active material precursor is controlled in such a manner that the pH gradually decreases as the nickel content in the mixed solution decreases.

[0023] According to another aspect of the present invention, there is provided a positive electrode for a lithium secondary battery, the positive electrode comprising the positive electrode active material according to the present invention.

[0024] According to another aspect of the present invention, there is provided a lithium secondary battery, the lithium secondary battery comprising the positive electrode according to the present invention.

[0025] Beneficial Effects

[0026] In the case where the transition metal has a concentration gradient in the active material particles and the ratio of the particle growth direction at the surface and the c-axis direction of the crystal satisfying a specific angle is high as in the positive electrode active material of the present invention, excellent output characteristics can be obtained even with a small amount of cobalt because the deterioration of the output characteristics caused by the reduction in the cobalt content can be minimized.

[0027] According to the present invention, the manufacturing cost of a secondary battery including the lithium transition metal oxide may be reduced by maintaining the cobalt content in the lithium transition metal oxide less than the manganese content.

[0028] In addition, since at least one transition metal contained in the lithium transition metal oxide has a concentration gradient that gradually changes from the center of the particle to its surface, structural stability is improved while having high capacity characteristics, thereby improving the life characteristics of the battery when the lithium transition metal oxide is used in the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a surface transmission electron microscope (TEM) image of the positive electrode active material prepared in Example 1 and a diffraction pattern of the crystal structure of the surface of the positive electrode active material confirmed by a selected area diffraction pattern (SADP);

[0030] Figure 2 is a surface TEM image of the positive electrode active material prepared in Comparative Example 1 and a diffraction pattern of the crystal structure of the surface of the positive electrode active material confirmed by SADP;

[0031] Figure 3 is a surface TEM image of the positive electrode active material prepared in Comparative Example 2 and a diffraction pattern of the crystal structure of the surface of the positive electrode active material confirmed by SADP;

[0032] Figure 4 is a charge and discharge curve graph of the secondary batteries prepared in Example 1 and Comparative Example 1; and

[0033] Figure 5 is a graph showing the capacity retention rate and the resistance increase rate during 300 cycles of the secondary batteries prepared in Example 1 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0034] Hereinafter, the present invention will be described in more detail.

[0035] It should be understood that the words or terms used in the specification and claims should not be interpreted as the meanings defined in commonly used dictionaries, and it will be further understood that, based on the principle that the inventor can appropriately define the meanings of words or terms to best explain the present invention, the words or terms should be interpreted as having meanings consistent with their meanings in the relevant technical background and technical concepts of the present invention.

[0036] Positive electrode active material

[0037] Lithium cobalt oxides having high operating voltage and excellent capacity characteristics have been used as positive electrode active materials for conventional lithium secondary batteries, but because lithium cobalt oxides have poor thermal properties due to unstable crystal structures caused by delithiation and are expensive, there are limitations in using a large amount of lithium cobalt oxides as power sources for medium and large-scale devices. Lithium nickel cobalt manganese oxides have been used to replace lithium cobalt oxides, but lithium nickel cobalt manganese oxides are limited in that discharge capacity and output characteristics decrease as the cobalt content is reduced in order to reduce manufacturing costs.

[0038] Therefore, the present inventors have found that because the mobility of lithium ions in the lithium transition metal oxide is improved by controlling at least one metal element contained in the lithium nickel cobalt manganese oxide in such a way that the concentration gradient gradually changes from the center of the particle to the surface thereof and the c-axis direction measured on the surface of the particle by transmission electron microscopy (TEM) analysis forms a specific angle with the growth direction of the particle at the measuring point, when the lithium nickel cobalt manganese oxide is used in a battery, the discharge capacity and output characteristics can be improved even if the cobalt content is reduced, thereby completing the present invention.

[0039] Hereinafter, the cathode active material according to the present invention will be described in detail.

[0040] The positive electrode active material according to the present invention is a positive electrode active material comprising a lithium transition metal oxide, wherein the content of cobalt in the lithium transition metal oxide is less than the content of manganese, wherein at least one of nickel, cobalt and manganese in the lithium transition metal oxide has a concentration gradient that gradually changes from the center of the particle to its surface, the positive electrode active material is in the form of secondary particles formed by the aggregation of primary particles, and at least 8 points on the surface of the positive electrode active material, the angle between the c-axis direction measured by TEM analysis and the growth direction of the particles at the measuring point satisfies a ratio of 85° to 95° of 60% or more.

[0041] Specifically, the positive electrode active material according to the present invention includes a lithium transition metal oxide having an average composition represented by Formula 1 below.

[0042] [Formula 1]

[0043] Li 1+aNi x Co y Mn z M 1 w O2

[0044] In Formula 1,

[0045] 0 ≤ a ≤ 0.3, 0.65 ≤ x < 1, 0 < y ≤ 0.35, 0 < z ≤ 0.35, 0 ≤ w ≤ 0.02 and y < z, and M 1 comprises at least one selected from the following: aluminum (Al), zirconium (Zr), magnesium (Mg), zinc (Zn), yttrium (Y), iron (Fe), and titanium (Ti).

[0046] Specifically, based on the total molar amount of transition metal elements other than lithium, the lithium transition metal oxide may contain nickel in an amount of 60 mol% or more to less than 100 mol%. When the amount of nickel in the lithium transition metal oxide is outside the above range, since the capacity of the positive electrode active material decreases, the positive electrode active material cannot be applied to an electrochemical device that requires high capacity. Within the above range, the larger the amount of nickel, the higher the capacity characteristics of the battery containing the lithium transition metal oxide are shown. However, the larger the amount of nickel, the relatively smaller the amount of cobalt and / or manganese, and thus the charge and discharge efficiency may decrease. Accordingly, based on the total molar amount of transition metal elements other than lithium, the lithium transition metal oxide may preferably contain nickel in an amount of 65 mol% to 75 mol%.

[0047] In addition, based on the total molar amount of transition metal elements other than lithium, the lithium transition metal oxide may contain manganese in an amount greater than 0 mol% to 35 mol% or less, preferably 15 mol% to 35 mol%, and most preferably 20 mol% or more to less than 35 mol%. When the amount of manganese is outside the above range, high capacity may not be achieved.

[0048] In addition, based on the total molar amount of transition metal elements other than lithium, the lithium transition metal oxide may contain cobalt in an amount greater than 0 mol% to 35 mol% or less, preferably greater than 0 mol% to 20 mol% or less, and most preferably greater than 0 mol% to 15 mol% or less. When the amount of cobalt is outside the above range and greater than 35 mol%, since the amount of cobalt is large, the total cost of raw materials may increase, and the reversible capacity may slightly decrease. When the amount of cobalt is 0 mol%, sufficient rate capability and output characteristics may not be exhibited.

[0049] According to the present invention, in the lithium transition metal oxide, the amount of manganese may be greater than the amount of cobalt. For example, in the case where the amount of manganese is less than or equal to the amount of cobalt, there may be limitations such as an increase in manufacturing cost due to an increase in the price of the cobalt raw material, a shortened lifespan, an increase in the rate of increase in resistance, and an increase in the amount of gas generated.

[0050] Specifically, in the lithium transition metal oxide, the molar ratio of cobalt: manganese may be in the range of greater than 1:1 to less than 1:10, preferably greater than 1:1 to less than 1:5, and more preferably greater than 1:1 to less than 1:3. For example, in the case where the molar ratio of cobalt: manganese in the lithium transition metal oxide is in the range of greater than 1:1 to less than 1:10, since a relatively small amount of cobalt is contained, not only an increase in cost can be suppressed, but also life characteristics, resistance characteristics, and gas generation can be improved.

[0051] If necessary, the doping element M can be selectively used 1 The positive electrode active material is doped.

[0052] The doping element M may be used without particular limitation. 1 , as long as it can help improve the structural stability of the positive electrode active material, wherein, for example, the doping element M 1 At least one selected from the group consisting of Al, Zr, Mg, Zn, Y, Fe and Ti may be included.

[0053] The doping element M may be included in an amount of 2 mol % or less (eg, 1 mol % to 2 mol %) based on the total moles of the transition metal elements except lithium. 1 For example, the doping element M is contained within the above amount range. 1 In the case of 1 It can be uniformly contained on the surface and inside of the positive electrode active material, and as a result, the structural stability of the positive electrode active material can be improved to improve output characteristics.

[0054] In addition, the positive electrode active material is in the form of secondary particles formed by aggregation of primary particles. Specifically, the positive electrode active material may include primary particles of a columnar structure growing from the center of the positive electrode active material in the surface direction.

[0055] Because the positive electrode active material contains primary particles of a columnar structure growing from the center of the positive electrode active material in the surface direction, the mobility of lithium ions on the surface of the positive electrode active material is improved, thereby improving the initial capacity characteristics and output characteristics when the positive electrode active material is used in a battery.

[0056] The columnar structure may have an aspect ratio of 2 to 5, for example, 3 to 5. In the case where the aspect ratio of the columnar structure satisfies the above range, capacity, lifespan, and resistance increase rate may be improved.

[0057] In addition, the positive electrode active material according to the present invention includes a lithium transition metal oxide having a layered structure. For example, at least 8 points on the surface of the positive electrode active material, the angle between the c-axis direction measured by TEM analysis and the growth direction of the particles at the measurement point satisfies 85° to 95°, and the ratio can be 60% or more.

[0058] In the case of a lithium transition metal oxide having a layered crystal structure, lithium ions move along a plane direction satisfying 85° to 95° with respect to the c-axis direction.

[0059] Therefore, in the case where the ratio of the angle between the c-axis direction and the growth direction of the lithium transition metal oxide particles satisfying 85° to 95° is less than 60%, because the growth direction of the lithium transition metal oxide particles and the plane direction satisfying 85° to 95° relative to the c-axis direction (lithium path direction) are not aligned on the surface of the positive electrode active material, the movement of lithium ions extracted from the interior of the positive electrode active material is hindered on the surface, so the mobility of lithium may be reduced. However, for the positive electrode active material of the present invention, since the measured ratio of the angle between the c-axis direction and the growth direction of the particles satisfying 85° to 95° is as high as 60% or more, the lithium ions extracted from the interior of the positive electrode active material can easily move to the outside of the positive electrode active material, thereby the mobility of lithium is excellent.

[0060] In this case, the crystal structure of the positive electrode active material can be observed by cutting the positive electrode active material and using a transmission electron microscope (TEM), and the c-axis direction of the positive electrode active material can be observed by fast Fourier transform (FFT) or selected area diffraction pattern (SADP).

[0061] In addition, at least one of nickel, cobalt and manganese contained in the positive electrode active material may be increased or decreased while having a concentration gradient that gradually changes from the center of the positive electrode active material particle to the surface of the particle. In this case, the concentration gradient slope of the transition metal may be constant. Nickel, cobalt and manganese contained in the positive electrode active material may each independently have a single concentration gradient slope value.

[0062] Specifically, the nickel contained in the positive electrode active material may have a concentration gradient that gradually decreases from the center of the positive electrode active material particle to the surface of the particle. In this case, the concentration gradient slope of nickel may be constant from the center of the positive electrode active material particle to its surface. As described above, in the case where nickel has a gradient in which a high concentration of nickel (Ni) is maintained at the center of the positive electrode active material particle and the concentration gradually decreases toward the surface of the particle, because the center of the particle contains a high content of nickel, the high capacity characteristics of the positive electrode active material can be maintained, and because the surface of the particle contains a low content of nickel to reduce the surface reactivity caused by the catalytic action of Ni, the structural stability of the positive electrode active material can be improved.

[0063] In addition, at least one of manganese and cobalt contained in the positive electrode active material may have a concentration gradient that gradually increases from the center of the positive electrode active material particle to the surface thereof. In this case, since the concentration of manganese and / or cobalt at the center of the positive electrode active material particle remains low and the concentration of manganese and / or cobalt increases relatively toward the surface of the positive electrode active material particle, excellent rate capability and life characteristics can be obtained.

[0064] For example, for conventional positive electrode active materials having a cobalt content less than a manganese content, the discharge capacity may decrease. However, because the positive electrode active material having a cobalt content less than a manganese content has a concentration gradient as in the present invention, the decrease in discharge capacity can be suppressed, and thus the decrease in low temperature characteristics and high temperature life characteristics can also be prevented.

[0065] Because the transition metal has a concentration gradient in which the concentration of the transition metal changes continuously according to the position in the positive electrode active material as in the present invention, there is no sudden change boundary area from the center of the positive electrode active material particle to its surface, thereby, its crystal structure is stable, thermal stability is improved, and when the positive electrode active material is used in a secondary battery, high capacity, long life and good thermal stability can be obtained. In addition, even if the content of cobalt is reduced, the capacity and output characteristics can be maintained. In the case where the slope of the concentration gradient of the transition metal is constant, the effect of improving structural stability can be further improved. In addition, because the concentration of each transition metal in the positive electrode active material particle changes due to the concentration gradient, the effect of improving battery performance of the positive electrode active material can be further improved by easily using the properties of the corresponding transition metal.

[0066] In the present invention, the expression "the concentration of the transition metal has a gradient that changes gradually (increases or decreases)" means that the transition metal has a concentration distribution in which the concentration of the transition metal changes gradually over the entire particle.

[0067] In addition, in the present invention, the concentration gradient structure and concentration of the metal in the lithium composite metal oxide particles can be identified by using methods such as electron probe microanalysis (EPMA), inductively coupled plasma atomic emission spectroscopy (ICP-AES) or time-of-flight secondary ion mass spectrometry (ToF-SIMS), wherein, specifically, etching is performed on the lithium composite metal oxide particles for 1000 seconds using argon gas, and the concentration gradient structure and concentration of the metal are measured by analyzing the amount of the element detected with the etching time from the start of etching using X-ray photoelectron spectroscopy (XPS).

[0068] As described above, for the positive electrode active material according to the present invention, since more than 60% of the crystals of the positive electrode active material have a c-axis direction that forms a specific angle with the surface of the particle, and the positive electrode active material has a concentration gradient even if the amount of cobalt is reduced, a positive electrode active material with excellent electrochemical properties can be provided at a low cost without reducing the capacity characteristics and output characteristics.

[0069] Method for preparing positive electrode active material

[0070] Next, a method for preparing a positive electrode active material according to the present invention will be described.

[0071] Specifically, in order to prepare the positive electrode active material according to the present invention, the method includes the following steps: preparing a first transition metal-containing solution and a second transition metal-containing solution, the first transition metal-containing solution containing a nickel raw material, the second transition metal-containing solution having a transition metal concentration different from that of the first transition metal-containing solution and containing a nickel raw material, a cobalt raw material, and a manganese raw material; preparing a positive electrode active material precursor by mixing the first transition metal-containing solution and the second transition metal-containing solution while gradually changing the mixing ratio of the first transition metal-containing solution to the second transition metal-containing solution; and mixing the positive electrode active material precursor with a lithium-containing raw material and sintering the mixture to synthesize the positive electrode active material. In this case, the step of preparing the positive electrode active material precursor is controlled in such a way that the pH gradually decreases as the nickel content in the mixed solution decreases.

[0072] Specifically, in order to prepare the positive electrode active material according to the present invention, a first transition metal-containing solution and a second transition metal-containing solution are first prepared, wherein the first transition metal-containing solution contains a nickel raw material, and the second transition metal-containing solution has a transition metal concentration different from that of the first transition metal-containing solution and contains a nickel raw material, a cobalt raw material and a manganese raw material.

[0073] If necessary, the first transition metal-containing solution may further selectively contain at least one of a cobalt raw material and a manganese raw material.

[0074] For example, the first transition metal-containing solution can be prepared by adding the nickel raw material to a solvent, particularly water or a mixture of water and an organic solvent (alcohol, etc.) that can be uniformly mixed with water, or after preparing an aqueous solution containing the nickel raw material, the aqueous solution can be mixed and used. In this case, each metal raw material is mixed in such a manner that the ratio of nickel:cobalt:manganese in the first transition metal-containing solution is in the range of (80 to 100):(0 to 10):(0 to 20) (e.g., (90 to 100):(0 to 5):(0 to 10)).

[0075] The second transition metal-containing solution comprises a nickel raw material, a cobalt raw material and a manganese raw material, and can be prepared in the same manner as the first transition metal-containing solution. In this case, each metal raw material is mixed in such a manner that the ratio of nickel:cobalt:manganese in the second transition metal-containing solution is in the range of (50 to 80):(10 to 30):(10 to 35) (e.g., (50 to 60):(20 to 30):(15 to 35)).

[0076] In this case, in the first transition metal-containing solution and the second transition metal-containing solution, the amount of manganese raw material may be greater than the amount of cobalt raw material. Therefore, for the prepared positive active material precursor particles, the amount of manganese is greater than the amount of cobalt in the entire particle, and because the positive active material precursor particles contain less cobalt raw material, the manufacturing cost can be reduced.

[0077] As the raw materials of nickel, cobalt and manganese, each sulfate, nitrate, acetate, halide, hydroxide or oxyhydroxide containing a metal element can be used, and the raw materials of nickel, cobalt and manganese can be used without particular limitation as long as these materials can be dissolved in the above-mentioned solvent such as water.

[0078] Specifically, the nickel raw material may include Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, fatty acid nickel salt or nickel halide, and a mixture of at least one of the above materials may be used.

[0079] In addition, the cobalt raw material may include Co(OH)2, CoOOH, CoSO4, Co(OCOCH3)2.4H2O, Co(NO3)2.6H2O or Co(SO4)2.7H2O, and a mixture of at least one of the above materials may be used.

[0080] In addition, the manganese raw material may include: manganese oxides such as Mn2O3, MnO2 and Mn3O4; manganese salts such as MnCO3, Mn(NO3)2, MnSO4, manganese acetate, manganese dicarboxylate, manganese citrate and fatty acid manganese salts; hydroxide oxide; and manganese chloride, and a mixture of at least one of the above materials may be used.

[0081] Subsequently, a cathode active material precursor is prepared by mixing the first transition metal-containing solution and the second transition metal-containing solution while gradually changing a mixing ratio of the first transition metal-containing solution to the second transition metal-containing solution.

[0082] In the preparation of the positive electrode active material precursor, the pH may be controlled in such a manner that the pH decreases as the nickel content in the mixed solution decreases.

[0083] For example, as the nickel content in the mixed solution decreases, the pH may be gradually decreased within a range of 13 to 9, preferably 12.5 to 9, and most preferably 12 to 10. In the case where the pH is controlled to be gradually decreased as the nickel content decreases during the preparation of the positive electrode active material precursor as described above, the c-axis direction on the surface of the finally prepared positive electrode active material particles can be effectively controlled.

[0084] Specifically, the positive electrode active material prepared while controlling the pH as described above can be formed in such a manner that at least 8 points on the surface of the positive electrode active material, the angle between the c-axis direction measured by TEM analysis and the growth direction at the measurement point satisfies 85° to 95° in a ratio of 60% or more.

[0085] More specifically, during the preparation of the positive electrode active material precursor, at the beginning of the reaction, the reaction is carried out at a pH of 11 to 13, preferably 11 to 12 or 11.5 to 12, and most preferably 11.7 to 12 to form the positive electrode active material precursor particle core, and in the later stage of the reaction, the reaction is carried out at a pH of 9 to 11, preferably 10 to 11 or 10.5 to 11, and most preferably 10.8 to 11 by adjusting the amount of the added ammonium ion complexing agent and the alkaline aqueous solution, thereby growing the positive electrode active material precursor particles. Therefore, the positive electrode active material precursor is not only in the form of secondary particles in which primary particles are aggregated, but also can contain primary particles of a columnar structure growing from the center of the positive electrode active material in the surface direction.

[0086] For example, during the preparation of the positive active material precursor, when the pH does not change and is the same throughout the particle, the core of the lithium transition metal oxide may be continuously formed during the coprecipitation reaction, and therefore, the growth of the primary particles may be reduced, thereby reducing the proportion of primary particles having a columnar structure. Therefore, the positive active material precursor particles prepared without changing the pH may have the form of secondary particles in which the primary particles are aggregated without orientation. In addition, when the core of the particle grows at a low pH and then the particle grows at a relatively high pH, ​​the particle size distribution may increase, thereby causing the inhomogeneity of the primary particles.

[0087] During the preparation of the positive electrode active material precursor, since the reaction is carried out in a state where only the first transition metal-containing solution is present at the start of the reaction, the initially prepared precursor particles have the composition of the first transition metal-containing solution, and thereafter, since the first transition metal-containing solution and the second transition metal-containing solution are mixed while gradually changing the ratio of the first transition metal-containing solution to the second transition metal-containing solution, the composition of the precursor particles also gradually changes to the composition of the second transition metal-containing solution from the center of the precursor particles to the surface thereof.

[0088] For example, when the reaction is carried out in such a manner that the amount of nickel is high and the amount of manganese and / or cobalt is low in the first transition metal-containing solution and the amount of nickel in the second transition metal-containing solution is lower than the amount of nickel in the first transition metal-containing solution and the amount of manganese and / or cobalt is higher than the amount of manganese and / or cobalt in the first transition metal-containing solution, the following precursor particles can be prepared, in which the concentration of nickel decreases while nickel has a continuous concentration gradient from the center of the active material particle in the direction of the particle surface, and the concentrations of manganese and cobalt each independently increase while manganese and cobalt have continuous concentration gradients from the center of the particle in the direction of the particle surface.

[0089] Therefore, the concentration gradient of the precursor particles can be controlled by adjusting the composition, mixing speed and mixing ratio of the first transition metal-containing solution and the second transition metal-containing solution so that the prepared precursor particles have a desired composition at a desired position, and the concentration gradient slope in this case can also be controlled.

[0090] In addition, by continuously mixing the first transition metal-containing solution and the second transition metal-containing solution, a precipitate in which the metal has a continuous concentration gradient from the center of the particle to its surface can be obtained in a single co-precipitation reaction process, and the concentration gradient of the metal in the active material precursor formed in this case and its slope can be easily adjusted by the composition and mixing feed ratio of the first transition metal-containing solution and the second transition metal-containing solution.

[0091] In addition, the concentration gradient of the transition metal element in the particle can be formed by controlling the reaction rate or reaction time. In order to produce a high-density state with a high concentration of a specific metal, it is desirable to increase the reaction time and reduce the reaction rate, and in order to produce a low-density state with a low concentration of a specific metal, it is desirable to reduce the reaction time and increase the reaction rate.

[0092] Subsequently, the cathode active material precursor is mixed with a lithium-containing raw material, and the mixture is sintered to synthesize a cathode active material.

[0093] The lithium-containing raw material is not particularly limited as long as it is a compound containing a lithium source, but preferably, at least one selected from the group consisting of lithium carbonate (Li2CO3), lithium hydroxide (LiOH), LiNO3, CH3COOLi and Li2(COO)2 can be used.

[0094] The amount of lithium-containing raw material used can be determined according to the amount of lithium and transition metal in the finally prepared positive electrode active material. Specifically, the lithium-containing raw material can be used in an amount such that the molar ratio of lithium contained in the lithium-containing raw material to the transition metal element contained in the precursor for the positive electrode active material (molar ratio of lithium / metal element) is in the range of 1.0 to 1.3 (for example, 1.0 to 1.2).

[0095] During the mixing of the positive electrode active material precursor and the lithium-containing raw material, if necessary, a doping element M may be selectively included. 1 Raw materials (including M 1 Contains at least one selected from the group consisting of Al, Zr, Mg, Zn, Y, Fe and Ti).

[0096] As mentioned above, it also contains the doping element M 1 In the case of the raw material, the doping element M may be contained in an amount of 2 mol% or less (eg, 1 mol% to 2 mol%) based on the total molar number of the positive electrode active material precursor. 1 raw material.

[0097] Subsequently, a positive electrode active material is prepared by sintering the mixture at 780° C. to 900° C., preferably 800° C. to 880° C., more preferably 810° C. to 870° C. for 20 to 25 hours. Since the sintering is performed within the above temperature range, crystallinity is improved, thereby preparing a positive electrode active material with improved structural stability.

[0098] Positive electrode for secondary battery

[0099] Next, a positive electrode for a lithium secondary battery is provided, the positive electrode including the positive electrode active material according to the present invention.

[0100] Specifically, a positive electrode for a lithium secondary battery is provided, the positive electrode comprising: a positive electrode collector; and a positive electrode active material layer formed on the positive electrode collector, wherein the positive electrode active material layer comprises the positive electrode active material according to the present invention.

[0101] In this case, since the positive electrode active material is the same as described above, a detailed description thereof will be omitted, and only the remaining configuration will be described in detail hereinafter.

[0102] The positive electrode current collector is not particularly limited as long as it has conductivity and does not cause adverse chemical changes in the battery, and for example: stainless steel; aluminum; nickel; titanium; calcined carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can generally have a thickness of 3 μm to 500 μm, and fine concavoconvexity can be formed on the surface of the current collector to improve the adhesion of the positive electrode active material. For example, the positive electrode current collector can be used in various shapes such as a film, a sheet, a foil, a net, a porous body, a foamed body, a non-woven fabric body, etc.

[0103] If necessary, the positive electrode active material layer may further contain a conductive material and, optionally, a binder in addition to the above-mentioned positive electrode active material.

[0104] In this case, the positive electrode active material may be included in an amount of 80 wt % to 99 wt % (eg, 85 wt % to 98.5 wt %) based on the total weight of the positive electrode active material layer. When the positive electrode active material is included in an amount within the above range, excellent capacity characteristics may be obtained.

[0105] The conductive material is used to provide conductivity to the electrode, wherein any conductive material can be used without particular limitation, as long as it has suitable electronic conductivity and does not cause adverse chemical changes in the battery. Specific examples of conductive materials can be: graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and carbon fiber; powder or fiber of metals such as copper, nickel, aluminum and silver; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, and any one of the above materials or a mixture of two or more thereof can be used. Based on the total weight of the positive electrode active material layer, the conductive material can generally be included in an amount of 0.1 wt % to 15 wt %.

[0106] Binder improves the adhesion between positive electrode active material particles and the adhesion between positive electrode active material and collector. Specific examples of binders can be polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-to-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or its various copolymers, and any one of the above materials or a mixture of two or more thereof can be used. Based on the gross weight of the positive electrode active material layer, the binder can be included in an amount of 0.1 wt % to 15 wt %.

[0107] In addition to using the above-mentioned positive electrode active material, the positive electrode can be prepared according to a typical method for preparing a positive electrode. Specifically, a composition for forming a positive electrode active material layer prepared by dissolving or dispersing the positive electrode active material and a selective binder and a conductive material (if necessary) in a solvent is coated on a positive electrode collector, and then the positive electrode can be prepared by drying and rolling the coated positive electrode collector.

[0108] The solvent may be a commonly used solvent in the art. The solvent may include dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone or water, and any one of the above materials or a mixture of two or more thereof may be used. Considering the coating thickness and manufacturing yield of the slurry, if the solvent can dissolve or disperse the positive electrode active material, the conductive material and the binder, and can allow for a viscosity that can provide excellent thickness uniformity during subsequent coating for preparing the positive electrode, the amount of the solvent used may be sufficient.

[0109] Furthermore, as another method, the positive electrode may be prepared by casting the composition for forming the positive electrode active material layer on a separate support and then laminating the film separated from the support on the positive electrode current collector.

[0110] Secondary battery

[0111] In addition, in the present invention, an electrochemical device comprising the positive electrode can be prepared. The electrochemical device can be a battery or a capacitor, for example, a lithium secondary battery.

[0112] The lithium secondary battery specifically includes a positive electrode, a negative electrode disposed facing the positive electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode is the same as the positive electrode described above, so its detailed description will be omitted, and only the remaining configuration will be described in detail below.

[0113] In addition, the lithium secondary battery may further selectively include: a battery container that accommodates an electrode assembly of a positive electrode, a negative electrode, and a separator; and a sealing member that seals the battery container.

[0114] In a lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector.

[0115] The negative electrode current collector is not particularly limited as long as it has high conductivity and does not cause adverse chemical changes in the battery, and for example: copper; stainless steel; aluminum; nickel; titanium; calcined carbon; copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.; and aluminum-cadmium alloy. In addition, the negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and similar to the positive electrode current collector, fine concavoconvexities may be formed on the surface of the current collector to improve the adhesion of the negative electrode active material. For example, the negative electrode current collector may be used in various shapes such as a film, a sheet, a foil, a net, a porous body, a foamed body, a non-woven fabric body, and the like.

[0116] The negative electrode active material layer selectively contains a binder and a conductive material in addition to the negative electrode active material.

[0117] Compounds that can reversibly intercalate and deintercalate lithium can be used as negative electrode active materials. Specific examples of negative electrode active materials can be: carbonaceous materials, such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; (semi)metallic materials that can form alloys with lithium, such as silicon (Si), aluminum (Al), tin (Sn), lead (Pb), zinc (Zn), bismuth (Bi), indium (In), magnesium (Mg), gallium (Ga), cadmium (Cd), Si alloys, Sn alloys, or Al alloys; metal oxides that can be doped or undoped with lithium, such as SiO β (0<β<2), SnO2, vanadium oxide and lithium vanadium oxide; or a composite material comprising a (semi)metallic material and a carbonaceous material, such as a Si-C composite material or a Sn-C composite material, and any one of the above materials or a mixture of two or more thereof can be used. In addition, a metallic lithium film can be used as a negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Typical examples of low-crystalline carbon can be soft carbon and hard carbon, and typical examples of high-crystalline carbon can be irregular, plate-like, flaky, spherical or fibrous natural graphite or artificial graphite; condensed graphite; pyrolytic carbon; mesophase pitch carbon fibers; mesophase carbon microbeads; mesophase pitch and high-temperature roasted carbon (such as coke derived from petroleum or coal tar pitch).

[0118] The negative electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer.

[0119] Binder is a component that helps to combine between conductive material, active material and current collector, wherein based on the total weight of negative electrode active material layer, binder is usually added in an amount of 0.1 wt % to 10 wt %. Examples of binders can be polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber, nitrile rubber, fluororubber and various copolymers thereof.

[0120] The conductive material is a component for further improving the conductivity of the negative electrode active material, wherein the conductive material can be added in an amount of 10% by weight or less (e.g., 5% by weight or less) based on the total weight of the negative electrode active material layer. The conductive material is not particularly limited as long as it has conductivity and does not cause adverse chemical changes in the battery, and conductive materials such as graphite, such as natural graphite or artificial graphite, carbon black, such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, conductive fibers, such as carbon fibers or metal fibers, carbon fluoride, metal powders, such as aluminum powder and nickel powder, conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers, conductive metal oxides, such as titanium oxide, or polyphenylene derivatives.

[0121] For example, the negative electrode active material layer can be prepared by coating a composition for forming a negative electrode prepared by dissolving or dispersing a selective binder and a conductive material and a negative electrode active material in a solvent on a negative electrode collector, and drying the coated negative electrode collector, or the negative electrode active material layer can be prepared by casting the composition for forming a negative electrode on a separate carrier and then laminating a film separated from the carrier on the negative electrode collector.

[0122] In a lithium secondary battery, the separator separates the negative electrode from the positive electrode and provides a path for the movement of lithium ions, wherein any separator can be used as a separator without particular restriction, as long as it is commonly used in lithium secondary batteries, in particular, a separator with high electrolyte moisture retention ability and low electrolyte ion migration resistance can be used. Specifically, a porous polymer film, such as a porous polymer film prepared by a polyolefin polymer (such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer) can be used; or a laminated structure having two or more layers in the above porous polymer film. In addition, a typical porous non-woven fabric can be used, such as a non-woven fabric formed by a high melting point glass fiber or a polyethylene terephthalate fiber. In addition, a coated separator containing a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a separator having a single layer or a multilayer structure can be selectively used.

[0123] In addition, the electrolyte used in the present invention may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel polymer electrolyte, a solid inorganic electrolyte or a molten inorganic electrolyte that can be used in the preparation of a lithium secondary battery, but the present invention is not limited thereto.

[0124] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0125] Any organic solvent can be used as an organic solvent without particular limitation, as long as it can be used as a medium through which ions participating in the electrochemical reaction of the battery can move. Specifically, as an organic solvent, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone can be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; or carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitrile such as R-CN (wherein R is a linear, branched or cyclic C2 to C20 hydrocarbon group, and may contain a double bond, an aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolanes; or cyclopentane sulfone. Among these solvents, carbonate solvents can be used, for example, a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ion conductivity and high dielectric constant that can improve the charge / discharge performance of the battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate, or diethyl carbonate) can be used. In this case, when the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9, the performance of the electrolyte can be excellent.

[0126] Lithium salts can be used without particular limitation, as long as they are compounds that can provide lithium ions used in lithium secondary batteries. Specifically, as lithium salts, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2 can be used. Lithium salts can be used in a concentration range of 0.1M to 2.0M. In the case where the concentration of the lithium salt is included in the above range, since the electrolyte can have appropriate conductivity and viscosity, the excellent performance of the electrolyte can be obtained, and the lithium ions can be efficiently moved.

[0127] In addition to the electrolyte components, in order to improve the life characteristics of the battery, suppress the reduction of the battery capacity and increase the discharge capacity of the battery, at least one additive may be added to the electrolyte, for example: halogenated alkylene carbonate compounds (such as difluoroethylene carbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N, N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol or aluminum chloride. In this case, the additive may be included in an amount of 0.1 wt % to 5 wt % based on the total weight of the electrolyte.

[0128] As described above, since the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, the lithium secondary battery is suitable for: portable devices such as mobile phones, notebook computers and digital cameras; and electric vehicles such as hybrid electric vehicles (HEV).

[0129] Thus, according to another embodiment of the present invention, a battery module including the lithium secondary battery as a unit battery and a battery pack including the battery module are provided.

[0130] The battery module or the battery pack can be used as a power source for at least one of the following medium and large-sized devices: power tools; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs); or power storage systems.

[0131] The shape of the lithium secondary battery of the present invention is not particularly limited, but a cylindrical type using a can, a prismatic type, a pouch type, or a coin type may be used.

[0132] The lithium secondary battery according to the present invention can be used not only in a battery cell used as a power source for small devices but also as a unit battery in a medium- and large-sized battery module including a plurality of battery cells.

[0133] Preferred Implementation

[0134] Hereinafter, the present invention will be described in detail according to specific embodiments. However, the present invention can be implemented in many different forms, and the present invention should not be construed as being limited to the embodiments set forth herein. Rather, these exemplary embodiments are provided to make this description thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0135] Example

[0136] Example 1

[0137] (Preparation of positive electrode active material)

[0138] A first transition metal-containing solution having a concentration of 2.3 M was prepared by mixing NiSO 4 and MnSO 4 in water in such an amount that the molar ratio of nickel:manganese was 95:5.

[0139] Furthermore, a second transition metal-containing solution having a concentration of 2.3 M was prepared by mixing NiSO 4 , CoSO 4 , and MnSO 4 in water in such an amount that the molar ratio of nickel:cobalt:manganese was 59:12.5:28.5.

[0140] The vessel containing the first transition metal-containing solution and the vessel containing the second transition metal-containing solution were connected to a 250 L reactor set at 53° C. In addition, a 25% NaOH solution and a 15% NH 4 OH aqueous solution were prepared and connected to the reactor, respectively.

[0141] Subsequently, 55 L of deionized water was placed in the reactor, and then the reactor was purged with nitrogen at a rate of 200 L / min to remove dissolved oxygen in the water and create a non-oxidizing atmosphere in the reactor. Thereafter, 50 mL of 25% NaOH was added to the reactor, and stirred at a speed of 280 rpm and a temperature of 53° C. to maintain the pH at 11.9.

[0142] Thereafter, while changing the ratio of the first transition metal-containing solution to the second transition metal-containing solution from 100 volume %: 0 volume % to 0 volume %: 100 volume %, the first transition metal-containing solution and the second transition metal-containing solution were added to the reactor at a rate of 63 mL / min. At the same time, while controlling the addition rate of the NaOH aqueous solution and the NH4OH aqueous solution to the reactor so that the pH in the reactor gradually decreased from 11.9 to 10.8, a coprecipitation reaction was performed for 24 hours to precipitate positive electrode active material precursor particles. The precipitated positive electrode active material precursor particles were separated and dried at 110° C. for 12 hours to prepare a Ni 0.7 Co 0.1 Mn 0.2 A positive electrode active material precursor represented by (OH)2, in which nickel, cobalt and manganese gradually change from the center of the particle to the surface thereof.

[0143] The positive electrode active material precursor thus obtained, Li2CO3 and doping elements Zr and Al are mixed in a molar ratio of 1:1.03:0.01:0.01, and sintered at 830°C for 10 hours in an oxygen atmosphere to prepare a positive electrode active material, which is doped with 2000 ppm of Zr and 1000 ppm of Al and has a concentration gradient in which the concentrations of nickel, cobalt and manganese gradually change from the center of the particle to the surface thereof.

[0144] (Preparation of positive electrode)

[0145] The positive electrode active material prepared above, Denka black conductive material and polyvinylidene fluoride (PVDF) binder were mixed in an N-methylpyrrolidone (NMP) solvent at a weight ratio of 95:2.5:2.5 to prepare a positive electrode slurry. Aluminum foil was coated with the positive electrode slurry prepared above, which was then rolled and dried at 120°C for 12 hours to prepare a positive electrode.

[0146] (Preparation of negative electrode)

[0147] Natural graphite as a negative electrode active material, a carbon black conductive material and a styrene butadiene rubber (SBR) binder were mixed at a weight ratio of 96:2:2 to prepare a negative electrode slurry. After a copper foil was coated with the negative electrode slurry and vacuum dried at 110° C. for 2 hours to prepare a negative electrode, roll pressing was performed.

[0148] (Preparation of Secondary Battery)

[0149] After preparing a coin cell type battery by a conventional method using the above-prepared positive and negative electrodes and a 20 μm thick polyethylene separator (F20BHE, Tonen Chemical Corporation), an electrolyte in which 1 M LiPF6 is dissolved in a mixed solvent of ethylene carbonate and dimethyl carbonate in a ratio of 1:1 (volume %) is injected to prepare a coin cell type lithium secondary battery.

[0150] Example 2

[0151] During the preparation of the positive electrode active material, a first transition metal-containing solution having a concentration of 2.3 M was prepared by mixing NiSO4 and MnSO4 in water in an amount such that the molar ratio of nickel:manganese was 95:5, and a second transition metal-containing solution having a concentration of 2.3 M was prepared by mixing NiSO4, CoSO4, and MnSO4 in water in an amount such that the molar ratio of nickel:cobalt:manganese was 55:20.5:24.5. In addition to preparing a positive electrode active material having Ni by using the first transition metal-containing solution and the second transition metal-containing solution, a first transition metal-containing solution having a concentration of 2.3 M was prepared. 0.65 Co 0.15 Mn 0.2 A positive electrode active material, a positive electrode including the same, and a lithium secondary battery were prepared in the same manner as in Example 1 except that the positive electrode active material precursor had an average composition of (OH) 2 and the positive electrode active material precursor was used.

[0152] Example 3

[0153] During the preparation of the positive electrode active material, a first transition metal-containing solution having a concentration of 2.3 M was prepared by mixing NiSO4 and MnSO4 in water in an amount such that the molar ratio of nickel:manganese was 95:5, and a second transition metal-containing solution having a concentration of 2.3 M was prepared by mixing NiSO4, CoSO4, and MnSO4 in water in an amount such that the molar ratio of nickel:cobalt:manganese was 55:13.5:31.5. In addition to preparing the positive electrode active material having Ni by using the first transition metal-containing solution and the second transition metal-containing solution, the first transition metal-containing solution and the second transition metal-containing solution were prepared. 0.65 Co 0.10 Mn 0.25 A positive electrode active material, a positive electrode including the same, and a lithium secondary battery were prepared in the same manner as in Example 1 except that the positive electrode active material precursor had an average composition of (OH) 2 and the positive electrode active material precursor was used.

[0154] Example 4

[0155] During the preparation of the positive electrode active material, a first transition metal-containing solution having a concentration of 2.3 M was prepared by mixing NiSO4 and MnSO4 in water in an amount such that the molar ratio of nickel:manganese was 95:5, and a second transition metal-containing solution having a concentration of 2.3 M was prepared by mixing NiSO4, CoSO4, and MnSO4 in water in an amount such that the molar ratio of nickel:cobalt:manganese was 55:17:28. In addition to preparing the positive electrode active material having Ni by using the first transition metal-containing solution and the second transition metal-containing solution, 0.65 Co 0.125 Mn 0.225 A positive electrode active material, a positive electrode including the same, and a lithium secondary battery were prepared in the same manner as in Example 1 except that the positive electrode active material precursor had an average composition of (OH) 2 and the positive electrode active material precursor was used.

[0156] Comparative Example 1

[0157] A solution containing transition metals having a concentration of 2.3 M was prepared by mixing NiSO 4 , CoSO 4 , and MnSO 4 in water in such an amount that the molar ratio of nickel:cobalt:manganese was 70:10:20.

[0158] While adding the transition metal-containing solution to a 250L reactor set at 53°C at a rate of 63 mL / min, an aqueous NaOH solution and an aqueous NH4OH solution were added at a rate of 35 mL / min and 50 mL / min, respectively, and a coprecipitation reaction was performed at a pH of 11.2 for 24 hours to precipitate positive electrode active material precursor particles. A positive electrode active material, a positive electrode containing the same, and a lithium secondary battery were prepared in the same manner as in Example 1 except that the positive electrode active material precursor precipitated above was used.

[0159] Comparative Example 2

[0160] A cathode active material, a cathode electrode and a lithium secondary battery including the same were prepared in the same manner as in Example 1, except that the pH in the reactor was maintained at 11.2 throughout the reaction.

[0161] Comparative Example 3

[0162] In addition to preparing a transition metal-containing solution having a concentration of 2.3 M by mixing NiSO4, CoSO4 and MnSO4 in water in an amount such that the molar ratio of nickel:cobalt:manganese is 65:15:20, and Ni is prepared by using the transition metal-containing solution. 0.65 Co 0.15 Mn 0.20 A positive electrode active material, a positive electrode including the same, and a lithium secondary battery were prepared in the same manner as in Comparative Example 1, except that a positive electrode active material precursor of (OH) 2 was prepared and the positive electrode active material precursor was used.

[0163] Comparative Example 4

[0164] In addition to preparing a transition metal-containing solution having a concentration of 2.3 M by mixing NiSO4, CoSO4 and MnSO4 in water in an amount such that the molar ratio of nickel:cobalt:manganese is 65:12.5:22.5, and preparing Ni by using the transition metal-containing solution 0.65 Co 0.125 Mn 0.225 A positive electrode active material, a positive electrode including the same, and a lithium secondary battery were prepared in the same manner as in Comparative Example 1, except that a positive electrode active material precursor of (OH) 2 was prepared and the positive electrode active material precursor was used.

[0165] Comparative Example 5

[0166] In addition to preparing a transition metal-containing solution having a concentration of 2.3 M by mixing NiSO4, CoSO4 and MnSO4 in water in an amount such that the molar ratio of nickel:cobalt:manganese is 65:20:15, Ni 0.65 Co 0.20 Mn 0.15 A positive electrode active material, a positive electrode including the same, and a lithium secondary battery were prepared in the same manner as in Comparative Example 1, except that a positive electrode active material precursor of (OH) 2 was prepared and the positive electrode active material precursor was used.

[0167] Comparative Example 6

[0168] In addition to preparing a transition metal-containing solution having a concentration of 2.3 M by mixing NiSO4, CoSO4 and MnSO4 in water in an amount such that the molar ratio of nickel:cobalt:manganese is 65:17.5:17.5, Ni 0.65 Co 0.175 Mn 0.175 A positive electrode active material, a positive electrode including the same, and a lithium secondary battery were prepared in the same manner as in Comparative Example 1, except that a positive electrode active material precursor of (OH) 2 was prepared and the positive electrode active material precursor was used.

[0169] Comparative Example 7

[0170] A first transition metal-containing solution having a concentration of 2.3 M was prepared by mixing NiSO 4 and MnSO 4 in water in such an amount that the molar ratio of nickel:manganese was 95:5.

[0171] Furthermore, a second transition metal-containing solution having a concentration of 2.3 M was prepared by mixing NiSO 4 , CoSO 4 , and MnSO 4 in water in such an amount that the molar ratio of nickel:cobalt:manganese was 55:27.5:17.5.

[0172] In addition to preparing Ni 0.65 Co 0.20 Mn 0.15 In addition to preparing a positive electrode active material precursor having an average composition of (OH)2 and a concentration gradient of Ni, Co and Mn gradually changing from the center of the particle to its surface and using the positive electrode active material precursor, a positive electrode active material and a positive electrode and a lithium secondary battery containing the same are prepared in the same manner as in Example 1.

[0173] Comparative Example 8

[0174] A first transition metal-containing solution having a concentration of 2.3 M was prepared by mixing NiSO 4 and MnSO 4 in water in such an amount that the molar ratio of nickel:manganese was 95:5.

[0175] Furthermore, a second transition metal-containing solution having a concentration of 2.3 M was prepared by mixing NiSO 4 , CoSO 4 , and MnSO 4 in water in such an amount that the molar ratio of nickel:cobalt:manganese was 55:24:21.

[0176] In addition to preparing Ni 0.65 Co 0.175 Mn 0.175 In addition to preparing a positive electrode active material precursor having an average composition of (OH)2 and a concentration gradient of Ni, Co and Mn gradually changing from the center of the particle to its surface and using the positive electrode active material precursor, a positive electrode active material and a positive electrode and a lithium secondary battery containing the same are prepared in the same manner as in Example 1.

[0177] Experimental Example 1: Confirmation of the surface properties of the positive electrode active material

[0178] The positive electrode active material particles prepared in Example 1 and Comparative Examples 1 and 2 were cut, the cross-section of the positive electrode active material was photographed using a transmission electron microscope (TEM), and the crystal structure of the surface of the positive electrode active material was identified by a selected area diffraction pattern (SADP).

[0179] Figure 1 , Figure 2 and Figure 3 TEM images and SADP of the positive electrode active materials prepared in Example 1 and Comparative Examples 1 and 2, respectively.

[0180] like Figure 1 As shown in , for the positive electrode active material prepared in Example 1, it can be confirmed that the surface portion contains primary particles of a columnar structure growing from the center of the positive electrode active material in the surface direction. In addition, TEM analysis was performed at 8 points on the surface of the positive electrode active material to confirm the lithium ion mobility on the surface of the positive electrode active material. Specifically, for the lithium transition metal oxide having a layered structure, lithium ions move in a direction relative to the c-axis direction ( Figure 1 The red arrow in the figure satisfies the plane direction from 85° to 95° ( Figure 1 The yellow arrow in the figure moves, Figure 1 The yellow arrow in the figure is called the lithium migration direction. Therefore, when the proportion of particles having an angle between the c-axis direction and the measured particle growth direction of 85° to 95° is as high as 60% or more (i.e., when Figure 1 When the lithium migration direction differs from the particle growth direction within ±5°, it can be confirmed that the lithium ion mobility on the surface of the positive electrode active material is excellent.

[0181] like Figure 1 As shown in FIG. 1 , as the result of TEM analysis at 8 points on the surface of the positive electrode active material (measured Figure 1 The particles marked by solid lines 1 to 8 in the TEM image of ) are measured in the c-axis direction ( Figure 1 The particles whose angle between the red arrow in the figure and the growth direction of the particles at the measurement point is 85° to 95° are Figure 1 Particles 1, 3, 4, 5, and 6 are located at the points marked in . Figure 1 Among the measured particles, particle 2 has a spinel structure, and the particle growth directions of particles 7 and 8 do not form 85° to 95° with the c-axis direction. That is, for the positive electrode active material prepared in Example 1, the proportion of the angles between the c-axis direction measured at 8 points on the surface and the particle growth direction at the measurement point satisfying 85° to 95° is 62.5%.

[0182] In contrast, Figure 2 As shown in , for the positive electrode active material prepared in Comparative Example 1, although the positive electrode active material is in the form of secondary particles formed by aggregation of primary particles, it can be confirmed that the shape of the primary particles in the surface portion is irregular. In addition, as a result of measuring the c-axis direction by TEM analysis of 8 points on the surface of the positive electrode active material, a spinel structure was present at 6 of the 8 points measured. It was found that the particle growth direction is consistent with the c-axis direction ( Figure 2 The angle between the two points (red arrows in the figure) meets the requirement of 85° to 95° only at one of the two points showing the layered structure (in Figure 2 Only particle 7 meets the requirement among the 8 points in the TEM image of FIG. 1 ). That is, for the positive electrode active material prepared in Comparative Example 1, the ratio in which the angle between the c-axis direction measured at 8 points on the surface and the particle growth direction at the measuring point satisfies 85° to 95° is 12.5%. For the spinel structure, since the lithium content is lower than that of the layered crystal structure, the capacity and life characteristics are deteriorated.

[0183] In addition, if Figure 3 As shown in , for the positive electrode active material prepared in Comparative Example 2, although the positive electrode active material is in the form of secondary particles formed by aggregation of primary particles, since the pH is not controlled during the preparation of the precursor, the rate of nucleus formation during the reaction increases, and thus in the surface portion of the positive electrode active material, the proportion of primary particles having a columnar structure growing from the center of the positive electrode active material in the surface direction is low. In addition, as a result of TEM analysis at 8 points on the surface of the positive electrode active material, the particles measured at 5 of the measured points have a spinel structure, and only the particles measured at one of the other three points have an angle between the growth direction of the particles at the measuring point and the c-axis direction that satisfies 85° to 95° ( Figure 3 That is, for the positive electrode active material prepared in Comparative Example 2, the ratio in which the angle between the c-axis direction measured at 8 points on the surface and the particle growth direction at the measuring point satisfied 85° to 95° was 12.5%.

[0184] Experimental Example 2: Charging and Discharging Efficiency of Secondary Batteries

[0185] For the secondary batteries prepared in Examples 1 to 4 and Comparative Examples 1 to 6, the charge and discharge efficiency was evaluated, and the results thereof are shown in Table 1 below.

[0186] Specifically, each of the secondary batteries prepared in Examples 1 to 4 and Comparative Examples 1 to 6 was charged to 4.30 V at a constant current of 0.1 C, left to stand for 20 minutes, and then discharged to a voltage of 3.0 V at a constant current of 0.1 C to observe the charge and discharge characteristics in the first cycle, and the results are shown in the following Tables 1 and Figure 4 middle.

[0187] [Table 1]

[0188] Charging capacity (mAh / g) Discharge capacity (mAh / g) efficiency(%) Example 1 215.6 197.7 91.7 Comparative Example 1 214.8 196.5 91.5 Comparative Example 2 215.3 195.5 90.8 Example 2 210.0 190.1 90.5 Example 3 209.5 190.4 90.8 Example 4 209.2 190.4 91.0 Comparative Example 3 205.1 181.4 88.4 Comparative Example 4 205.3 177.1 86.2 Comparative Example 5 204.6 185.3 90.5 Comparative Example 6 205.4 185.1 90.1

[0189] Refer to Table 1 and Figure 4 From the results of Example 1 and Comparative Examples 1 and 2, it can be confirmed that, for the positive electrode active material containing the same amount of nickel, for Example 1 with a concentration gradient in which more than 60% of the c-axis direction forms a specific angle with the growth direction of the primary particles present on its surface, the efficiency is improved compared with Comparative Example 1 without a concentration gradient and a specific orientation and Comparative Example 2 with a concentration gradient but no specific orientation.

[0190] In addition, referring to the results of Examples 2 to 4 and Comparative Examples 3 to 6 in Table 1, for the secondary batteries without concentration gradient prepared in Comparative Examples 3 and 4 (in the secondary batteries, for the same nickel content, the cobalt content in the lithium transition metal oxide is lower than the manganese content), it can be confirmed that the capacity decreases as the cobalt content decreases. In contrast, it can be confirmed that the secondary battery prepared by using the positive electrode active material having a concentration gradient and a specific orientation even if the cobalt content in the lithium transition metal oxide is lower than the manganese content as in Examples 2 to 4 has an efficiency equal to or better than that of the secondary batteries of Comparative Examples 4 and 5 in which the cobalt content in the lithium transition metal oxide is greater than or equal to the manganese content.

[0191] Experimental Example 3: Confirmation of output characteristics of secondary batteries

[0192] The low temperature (-10°C) output characteristics of the lithium secondary batteries prepared in Examples 1 and 2 and Comparative Examples 1 to 6 were confirmed. Specifically, each of the lithium secondary batteries prepared in Examples 1 and 2 and Comparative Examples 1 to 6 was charged at a constant current of 0.33C at room temperature (25°C), and then discharged at a constant current of 0.4C for 22.5 minutes to measure the voltage drop for 1350 seconds, and the results are shown in Table 2 below.

[0193] [Table 2]

[0194]

[0195] Referring to Example 1 and Comparative Examples 1 and 2 in Table 2, for the same composition, for Example 1 having a concentration gradient in which more than 60% of the c-axis direction forms a specific angle with the growth direction of the primary particles present on its surface, it can be confirmed that the voltage drop rate is lower than that of the secondary battery containing the positive electrode active material of Comparative Example 1 having no concentration gradient and a specific orientation between the c-axis direction and the growth direction of the particles present on its surface, and the secondary battery containing the positive electrode active material of Comparative Example 2 having a concentration gradient but not having a specific orientation between the c-axis direction and the growth direction of the primary particles present on its surface.

[0196] In the positive electrode active material containing the same amount of nickel as in Example 2 and Comparative Examples 3 to 6, it can be confirmed that Comparative Examples 3 and 4 without a concentration gradient, in which the content of cobalt in the lithium transition metal oxide is lower than the content of manganese, have a higher voltage drop rate due to the reduction in the cobalt content, compared with Comparative Example 5 in which the content of cobalt in the lithium transition metal oxide is greater than the content of manganese.

[0197] In contrast, for Example 2 having a concentration gradient in which the cobalt content in the lithium transition metal oxide is lower than the manganese content but the growth direction of the particles present on its surface forms a specific angle with the c-axis, it can be confirmed that even if the cobalt content is reduced, the voltage drop rate is still better due to the uniformity of the primary particles, compared with Comparative Example 5 containing the same amount of nickel and Comparative Example 3 having the same composition.

[0198] Experimental Example 4: Evaluation of High-Temperature Life and Resistance Characteristics of Secondary Batteries

[0199] The life characteristics and resistance characteristics of the secondary batteries containing the positive electrodes prepared in Examples 1 to 4 and Comparative Examples 1 to 8 were measured. Specifically, each secondary battery prepared in Examples 1 to 4 and Comparative Examples 1 to 8 was charged to 4.25V at a constant current of 1C at 45°C, and the charge was cut off at 3C. Thereafter, it was discharged to a voltage of 3.0V at a constant current of 1C. The charging and discharging behavior was set as one cycle, and after repeating the cycle 300 times, the capacity retention rate and resistance increase rate of the secondary batteries according to Examples 1 to 4 and Comparative Examples 1 to 8 with the cycle were measured. Regarding the life characteristics, the capacity in the 300th cycle was divided by the initial capacity and then multiplied by 100 to calculate the value. Regarding the resistance characteristics, after the resistance in the 300th cycle was divided by the initial resistance and multiplied by 100 to calculate the value, the results are shown in the following Tables 3 and Figure 5 middle.

[0200] [Table 3]

[0201]

[0202] As shown in Table 3 and Figure 5As shown in the results of Example 1 and Comparative Examples 1 and 2, in the positive electrode active material containing the same amount of nickel, it can be confirmed that the life characteristics and resistance characteristics of the secondary battery prepared in Example 1 are improved compared with the secondary battery of Comparative Example 1 containing the same nickel content but the lithium transition metal oxide does not have a concentration gradient and the secondary battery of Comparative Example 6 which does not have a specific orientation due to pH control during the preparation of the lithium transition metal oxide.

[0203] In addition, for the secondary batteries containing the same nickel content prepared in Examples 2 to 4 and Comparative Examples 3 to 8, it can be confirmed that the life characteristics and resistance characteristics are improved compared to the secondary batteries of Comparative Examples 3, 4 and 6 without a concentration gradient in which the content of cobalt in the lithium transition metal oxide is less than or equal to the content of manganese. In addition, it can be confirmed that the life characteristics and resistance characteristics are improved compared to the secondary battery of Comparative Example 5 in which the content of cobalt in the lithium transition metal oxide is greater than the content of manganese but without a concentration gradient.

[0204] For the secondary batteries prepared in Examples 2 to 4, the life characteristics are poor compared with the secondary batteries of Comparative Examples 7 and 8 with a concentration gradient in which the cobalt content in the lithium transition metal oxide is greater than or equal to the manganese content, especially the secondary battery of Comparative Example 7 with the highest cobalt content, but it can be confirmed that compared with the secondary batteries of Comparative Examples 7 and 8, the resistance characteristics are improved because the lithium ion mobility is improved by having a specific orientation.

Claims

1. A positive electrode active material, the positive electrode active material comprising: A lithium transition metal oxide having an average composition represented by Formula 1, wherein the content of cobalt in the lithium transition metal oxide is less than the content of manganese, wherein nickel contained in the positive electrode active material has a concentration gradient that gradually decreases from the center of the positive electrode active material particles to the surface of the particles, and manganese and cobalt contained in the positive electrode active material have a concentration gradient that gradually increases from the center of the positive electrode active material particles to the surface, wherein the molar ratio of cobalt:manganese in the lithium transition metal oxide is in the range of 1:1.8 to 1:3, the positive electrode active material is in the form of secondary particles formed by aggregation of primary particles, and wherein at at least 8 points on the surface of the positive electrode active material, the proportion of the angle between the c-axis direction measured by transmission electron microscope (TEM) analysis and the growth direction of the particles at the measurement points satisfying 85° to 95° is 60% or more: [Formula 1] Li 1+a Ni x Co y Mr z M 1 w O2 in, In Formula 1, 0≤a≤0.3, 0.65≤x<1, 0<y≤0.35, 0<z≤0.35, 0≤w≤0.02 and y<z, and M 1 Contains at least one selected from the group consisting of Al, Zr, Mg, Zn, Y, Fe and Ti.

2. The positive electrode active material according to claim 1, wherein the positive electrode active material contains primary particles having a columnar structure that grow in the surface direction from the center of the positive electrode active material in the surface portion.

3. The positive electrode active material according to claim 1, wherein based on the total molar number of transition metal elements other than lithium, the lithium transition metal oxide represented by Formula 1 contains cobalt in an amount of 15 mol% or less.

4. The positive electrode active material according to claim 1, wherein based on the total molar number of transition metal elements other than lithium, the lithium transition metal oxide represented by Formula 1 contains manganese in an amount of 20 mol% or more and less than 35 mol%.

5. A method for preparing a positive electrode active material, the method comprising the following steps: Preparing a first transition metal-containing solution and a second transition metal-containing solution, the first transition metal-containing solution containing a nickel raw material, and the second transition metal-containing solution having a transition metal concentration different from that of the first transition metal-containing solution and containing a nickel raw material, a cobalt raw material, and a manganese raw material; Preparing a positive electrode active material precursor by mixing the first transition metal-containing solution and the second transition metal-containing solution while gradually changing the mixing ratio thereof; and Mixing the positive electrode active material precursor with a lithium-containing raw material and sintering the mixture to synthesize a positive electrode active material, wherein the step of preparing the positive electrode active material precursor is controlled in such a manner that the pH gradually decreases as the nickel content in the mixed solution decreases, wherein at at least 8 points on the surface of the positive electrode active material, the proportion of the angle between the c-axis direction measured by transmission electron microscope (TEM) analysis and the growth direction of the particles at the measurement points satisfying 85° to 95° is 60% or more.

6. The method of claim 5, wherein the molar ratio of nickel:cobalt:manganese in the first transition metal-containing solution is in the range of (80 to 100):(0 to 10):(0 to 20).

7. The method of claim 5, wherein the molar ratio of nickel:cobalt:manganese in the second transition metal-containing solution is in the range of (50 to 80):(10 to 30):(10 to 35).

8. The method according to claim 5, wherein the pH is gradually decreased within the range of 13 to 9.

9. The method according to claim 5, further comprising adding a doping element M during mixing the positive electrode active material precursor with the lithium-containing raw material. 1 Raw materials (including M 1 Contains at least one selected from the group consisting of Al, Zr, Mg, Zn, Y, Fe and Ti). 10 . A positive electrode for a lithium secondary battery, comprising the positive electrode active material according to claim 1 . 11 . A lithium secondary battery comprising the positive electrode according to claim 10 .